Emalie limuzyjskie z kolekcji Pałacu Muzeum w Wilanowie – zastosowanie metod analitycznych w badaniu techniki wykonania - Podgórski, Andrzej; Tomaszewska-Szewczyk, Alina (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2013)
Enamel is a glass alloy modified by the addition of flux and coloring metal compounds. The ratio of these components is suitable for its properties to coating the metal base. Labeled elements in the analyzed samples are not only the basis of mineral filler used in the manufacture of enamel or flux component, but they also helps to obtain specific mechanical and/or physicochemical properties. There are several methods decorating items in this technique. Among them special attention due to artistic and technical aspect are enamels from Limoges, which were initiated by enamellers from Limoges. The new technique was an opportunity to naturalistic rendering of the world. Dishes were being coated with images about functional features. Copper base in this technique is covered with the monochromatic, dark enamel. It constituted the background of the picturesque in the technique en grisaille, made with characteristic white gloss paint (blanc de Limoges) applied with a brush and the removed by a needle. In the XIX-th century, the fashion for renaissance enamels from Limoges returned. Many collections was created in this time for example August’s Poniatowski, later it was called as Wilanów collections. XVI and XVII eternal enamels from Limoges have been subjected to instrumental analysis with the application of scaning electron microscopy and the X-ray fluorescence. This set belongs to the collection of the Museum- Palace in Wilanów. The results of stratigraphy and composition of individual colourful enamel layers provided valuable information about the technique of implementation of historical objects, essential while performing conservation works.